Exercise‐induced metabolic fluctuations influence AMPK, p38‐MAPK and CaMKII phosphorylation in human skeletal muscle. Issue 9 (9th September 2015) - Combes, Adrien; Dekerle, Jeanne; Webborn, Nick; Watt, Peter; Bougault, Valérie; Daussin, Frédéric N.
Abstract During transition from rest to exercise, metabolic reaction rates increase substantially to sustain intracellular ATP use. These metabolic demands activate several kinases that initiate signal transduction pathways which modulate transcriptional regulation of mitochondrial biogenesis. The purpose of this study was to determine whether metabolic fluctuations per se affect the signaling cascades known to regulate peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α). On two separate occasions, nine men performed a continuous (30‐min) and an intermittent exercise (30 × 1‐min intervals separated by 1‐min of recovery) at 70% of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2xswwfr4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />V˙O2peak</alternatives>. Skeletal muscle biopsies from the vastus lateralis were taken at rest and at +0 h and +3 h after each exercise. Metabolic fluctuations that correspond to exercise‐induced variation in metabolic rates were determined by analysis of VO2 responses. During intermittent exercise metabolic fluctuations were 2.8‐fold higher despite identical total work done to continuous exercise (317 ± 41 vs. 312 ± 56 kJ after intermittent and continuous exercise, respectively). Increased phosphorylation of AMP‐activated protein kinase (AMPK) (~2.9‐fold, P < 0.01), calcium/calmodulin‐dependent protein kinase II (CaMKII) (~2.7‐fold, P < 0.01) and p38‐mitogen‐activated protein kinase (MAPK) (~4.2‐fold, P < 0.01) occurred immediately in both exercises and to a greater extent after the intermittent exercise (condition x time interaction, P < 0.05). A single bout of intermittent exercise induces a greater activation of these signaling pathways regulating PGC‐1α when compared to a single bout of continuous exercise of matched work and intensity. Chronic adaptations to exercise on mitochondria biogenesis are yet to be investigated.